2014
DOI: 10.1021/jp507720h
|View full text |Cite
|
Sign up to set email alerts
|

Toward a Silver–Alumina Model System for NOx Reduction Catalysis

Abstract: The growth and morphology of Ag deposited on NiAl(110) and on oxidized NiAl(110) have been investigated by a combination of scanning tunneling microscopy (STM) and high-resolution core-level spectroscopy (HRCLS). While the STM measurements reveal complete wetting and a bilayer growth on clean NiAl(110), Ag nanoparticles with a minimum size of 5 nm were obtained on the oxidized NiAl(110). The difference in Ag growth mode on clean and oxidized NiAl( 110) is supported by Ag 3d HRCLS. The binding energy for Ag on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…However, the formation mechanism of isocyanate species is still debated. Previous studies reached similar conclusions that the initial step may be the dissociation of the NO molecule on the surface, and this may be followed by attack of a CO molecule to form the surface isocyanate species. But more recent studies indicate that the breaking of the NO bond may be directly assisted by the attack of CO molecule to form a surface nitride species, which then reacts with CO to form the isocyanate NCO species. ,,, …”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…However, the formation mechanism of isocyanate species is still debated. Previous studies reached similar conclusions that the initial step may be the dissociation of the NO molecule on the surface, and this may be followed by attack of a CO molecule to form the surface isocyanate species. But more recent studies indicate that the breaking of the NO bond may be directly assisted by the attack of CO molecule to form a surface nitride species, which then reacts with CO to form the isocyanate NCO species. ,,, …”
Section: Introductionmentioning
confidence: 86%
“…13−21 But more recent studies indicate that the breaking of the NO bond may be directly assisted by the attack of CO molecule to form a surface nitride species, which then reacts with CO to form the isocyanate NCO species. 8,12,22,23 The reactions of metal atoms with NO and CO serve as the simplest model in understanding the intrinsic mechanism of catalytic NO and CO reduction processes. Previous matrix isolation infrared spectroscopic studies on the reactions of transition-metal atoms with CO and NO mixtures show that some metal atoms react with NO and CO to form unsaturated metal carbonyl nitrosyl complexes.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Among them, several formulations based on Ag/Al 2 O 3 catalysts have proved to be particularly active [44,[48][49][50] and although there is still some speculation about the mechanism for NO x reduction, -CN and -NCO species have been proposed as key…”
Section: Discussionmentioning
confidence: 99%
“…In order to reduce this concentration, heterogeneous catalysts that promote the reaction of NO x with reductant reagents in the atmosphere, like CO, hydrocarbons or alcohols have successfully been developed [51]. Among them, several formulations based on Ag/Al 2 O 3 catalysts have proved to be particularly active [48,[52][53][54] and although there is still some speculation about the mechanism for NO x reduction, -CN and -NCO species have been proposed as key intermediates [46]. According to these authors, when CO is used as reductant, the process starts with the adsorption of CO and NO x on the same Ag NP where they are both dissociated.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the Ni catalyst as an important electroactive material not only presents great adsorption ability for a gas molecule (such as the ethyne relative to Rh, Pd, and Pt) but also displays great catalytic potentials in steam-reforming hydrogenation of carbon dioxide, NO dissociation, , and CH 3 OH dissociation . Among all the relevant low-cost deNO x catalysts that have been investigated by experimental and density functional theory (DFT) calculation methods, ,, it is found that the Ni catalyst shows a much better low-temperature NO dissociation activity than the noble metals. For example, the experimental investigation for NO reduction by hydrogen showed that the Ni/Al 2 O 3 catalyst realized 95% NO conversion at low temperature .…”
Section: Introductionmentioning
confidence: 99%